(3cJGH aj GdCOYjI hGdRjGQGJ, hJNJdW ajg GdYQHjI HGdaGQSjIs - (3eLghds
(3ChdgG (B:s
(3eHJhQ GdChd, hjHOC GdehLhO efg HYOI UaMGJ HGddZI GdaGQSjI hHYOgG JHOC GdCOYjI HGddZI GdYQHjI(B: ...(3Gddge jGaGQL Gdge hefaS GdZe(B...s
(3BNQgG (B:s
(3hBNQg(B: ...(3CjgG GdbGFe GdegOj jG MLI Gddg Ydi Ndbg EfG JhLgfG hGSJTaYfG hJhSdfG Hc Edi Gddg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs